2011
DOI: 10.1039/c0nr00560f
|View full text |Cite
|
Sign up to set email alerts
|

Nanosensors: towards morphological control of gas sensing activity. SnO2, In2O3, ZnO and WO3case studies

Abstract: Anisotropy is a basic property of single crystals. Dissimilar facets/surfaces have different geometric and electronic structure that results in dissimilar functional properties. Several case studies unambiguously demonstrated that the gas sensing activity of metal oxides is determined by the nature of surfaces exposed to ambient gas. Accordingly, a control over crystal morphology, i.e. over the angular relationships, size and shape of faces in a crystal, is required for the development of better sensors with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
248
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 411 publications
(257 citation statements)
references
References 79 publications
5
248
0
4
Order By: Relevance
“…The BET specific surface areas of CuAlO 2 flowers and hexagonal structures were calculated to be 59. 8 , respectively. The results suggest that the surface area distribution of the CuAlO 2 hexagonal structure is larger than that of flowers, due to its dimension formed by the aggregation of the CuAlO 2 nanoparticles, and hence could show good sensing behavior.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The BET specific surface areas of CuAlO 2 flowers and hexagonal structures were calculated to be 59. 8 , respectively. The results suggest that the surface area distribution of the CuAlO 2 hexagonal structure is larger than that of flowers, due to its dimension formed by the aggregation of the CuAlO 2 nanoparticles, and hence could show good sensing behavior.…”
Section: Resultsmentioning
confidence: 99%
“…3−7 Ozone (O 3 ) is a powerful oxidizing reagent and a very strong disinfectant whose appearance in the atmosphere is very harmful for human health. 8 As per the World Health Organization (WHO), the air quality guidelines for ozone exposure of 1 ppm cause burning eyes, headaches, and irritation to the respiratory passages. An individual, if exposed to 0.2 ppm or 200 ppb of O 3 for 2 h, will sustain a loss of 20% in breathing capacity and, if exposed to 1 ppm of O 3 for 6 h, will suffer an attack of bronchitis.…”
Section: Introductionmentioning
confidence: 99%
“…21 Recently, several studies have demonstrated that the electrical response and the selectivity of nanostructured metaloxide gas sensors are signicantly affected by the shape of the nanocrystals and specically by their exposed crystal surfaces. 10,20,25,26 In this perspective, efforts have been devoted to the development of morphology controlled semiconductor oxides with specic exposed crystal surfaces. 20,[25][26][27] For instance, Han et al 26 demonstrated that shape controlled WO 3 nanocrystals with highly exposed {020} facets exhibit higher sensitivity towards 1-butylamine compared to nanoparticles with other prominent facets.…”
Section: 1322-24mentioning
confidence: 99%
“…10,20,25,26 In this perspective, efforts have been devoted to the development of morphology controlled semiconductor oxides with specic exposed crystal surfaces. 20,[25][26][27] For instance, Han et al 26 demonstrated that shape controlled WO 3 nanocrystals with highly exposed {020} facets exhibit higher sensitivity towards 1-butylamine compared to nanoparticles with other prominent facets. The differences in the gas sensing capability were attributed to the presence of coordinatively unsaturated cations on the {020} surfaces, i.e.…”
Section: 1322-24mentioning
confidence: 99%
“…generally dominated by nonpolar or polar facets that provide a specific electronic structure at the surface. Thus, the morphological control of ZnO as well as other metal oxides has found to be particularly important in surface-dependent applications such as gas sensing, as it allows the tuning of the properties of gas sensitive materials [1]. The first stage toward the morphological control of structures includes the use of synthetic methods (e.g., bottom-up) capable of producing well-defined crystals, with uniform size, shape, and surface structure.…”
Section: Introductionmentioning
confidence: 99%